Czerwony horror. Niedźwiedzie gody (1926) Konstantina Eggerta i Władimira Gardina jako pierwszy film grozy w kinematografii radzieckiej - Cybulski, Marcin (Slavia Orientalis, 2025)
The horror genre began to develop in Russia almost simultaneously with the emergence of its indigenous film industry. During the final years of the Russian Empire, thousands of short films were produced, some of which incorporated elements of horror. However, in post-revolutionary Russia and the USSR, support for genre cinema, particularly horror, significantly diminished. Despite this decline, The Bear's Wedding (1926), directed by Konstantin Eggert and Vladimir Gardin, achieved notable box office success. The film is an adaptation of Prosper Mérimée's novella Lokis: The Manuscript of Professor Wittembach, albeit with a significantly altered plot. Through its narrative structure and cinematic techniques, The Bear's Wedding stands out as the first full-length horror film in Soviet cinema, earning a significant place in the history of both Soviet and European cinema.